Ketamine: A Neuroanesthesiologist's Friend or Foe? - Luthra, Ankur; Rath, Girija Prasad (Journal of Neuroanaesthesiology and Critical Care, 2018)
Ketamine, an N-methyl-D-aspartate (NMDA) receptor antagonist, introduced into clinical practice six decades ago, has often been the worst fear of a neuroanesthesiologist due to its concerns of causing a rise in intracranial pressure and increasing cerebral blood volume. However, the recent literature clarifies that it may have a beneficial role, even in neurosurgical patients, because of its propensity to cause neuroprotection through antiglutamatergic action on the NMDA receptors in the ischemic brain. Apart from having an anticonvulsive role in refractory status epilepticus, its inherent property of increasing blood flow to the ischemic areas offers protection to the penumbral zone, thus preventing secondary brain injuries. Also, it has been widely used as an analgesic at subanesthetic doses post spine surgeries. Recently, enough scientific evidence has been published in favor of ketamine establishing the fact that it does not cause a rise in intracranial pressure when the patient is mechanically ventilated and normocarbia is maintained. It has also been used during evoked potential monitoring as it amplifies signals even under general anesthesia and proves to be quite effective during neuromonitoring. However, its adverse effects of increasing muscle tone, excessive salivation, emergence delirium, agitation, and “out of body” experiences with long-term psychomimetic effects and potential to cause addiction have precluded its widespread use.This review on ketamine summarizes the benefits of using it in neurosurgical anesthesia with the aim of removing the fears we had in the past, which did not seem to be evidence based.
Keywords: N-methyl-D-aspartate antagonist; excitotoxicity; neuroprotection; neuroinflammation